The neural substrates of bruxism: current knowledge and clinical implications - Uchima Koecklin, Karin Harumi; Aliaga-Del Castillo, Aron; Li, Peng (Frontiers in Neurology, 2024)
Bruxism is a complex orofacial behavior that can occur during sleep or wakefulness, characterized by the involuntary grinding or clenching of teeth, involving repetitive activity of the jaw muscles. Its etiology is multifactorial, influenced by genetic, psychological, physiological, and lifestyle factors. While the mild bruxism may not necessitate treatment, severe bruxism can lead to significant consequences, including tooth damage, jaw pain, fatigue, and headaches. The bruxism has been associated with medical conditions, such as stress, anxiety, sleep disorders, and various neurological disorders; however, the exact pathophysiology remains elusive. Although the central nervous system is strongly implicated in the development of bruxism, specific neural substrates have not yet been conclusively established. Furthermore, there is evidence to suggest that individuals with bruxism may exhibit neural plasticity, resulting in the establishment of distinct neural circuitry that control the jaw movements. The application of various neurophysiological techniques in both clinical and pre-clinical studies provides valuable insights into the neural mechanisms underlying bruxism. This review aims to comprehensively examine the current literature on the neural pathways involved in bruxism, with the goal of improving the clinical approach and therapeutics for this condition. A deeper understanding of the neural circuitry controlling bruxism holds the potential to advance future treatment approaches and improve the management of patients with bruxism.